Tinjauan Sistematik: Efektivitas dan Keamanan Fecal Microbiota Transplantation pada Infeksi Clostridium difficile Berulang pada Anak - Rosdiana, Fetri; Suswati, Enny; Kusuma, Irawan Fajar (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Background: Recurrent Clostridium difficile infection (RCDI) continues to increase in incidence and severity around the world. Fecal microbiota transplantation (FMT) is commonly used to treat RCDI in adults, but its efficacy and safety in the pediatric population are infrequently studied. Here, we performed a systematic review to evaluate the efficacy and safety of FMT for RCDI in children.Methods: Systematic literature search was performed using PubMed, Science Direct, Nature, Cochrane Library, and Springer to identify original studies in English language published from 2010-2020. The clinical resolution, bacterial resolution, and failure of therapy were calculated as indicators of efficacy of FMT. Adverse events were also calculated as indicators of FMT safety.Results: A total of 21 studies, with 498 pediatric patients were included in this review. There were 418/498 (84%) patients reported clinical and bacterial resolution. There were 67/498 (13%) patients who experienced FMT-related adverse events, with 97% of them had mild adverse event. There was one patient who reported FMT-related serious adverse events which were aspiration pneumonia and dehydration.Conclusion: We found evidence that supports the efficacy and safety of the use of FMT for treatment of recurrent C. difficile infection in children.